Psychological safety in health professions education: insights and strategies from a global community of practice - Dong, Chaoyan; Altshuler, Lisa; Ban, Nobutaro; Wong, Lee Yuen; Mohammed, Fatima Elbasri Abuelgasim; Tang, Chao Tian; Kachur, Elizabeth (Frontiers in Medicine, 2025)
Psychological safety is the belief that one will not be punished or humiliated for speaking up, sharing ideas, raising concerns, or making mistakes. There are various threats to psychological safety in health professions education (HPE). This commentary applies Clark’s model of psychological safety (Inclusion Safety, Learner Safety, Contributor Safety, Challenger Safety) to five different HPE settings (classroom instructions, clinical training, simulation-based training, online instructions, interprofessional education). Setting-specific threats and strategies for enhancing psychological safety are discussed.